Aerial manipulation based on force and torque sensory feedback - Buzzatto, João Pedro Sansão (2019)
The interest of the research community in studying Unmanned Aerial Vehicles (UAV) have increase greatly in teh last decade. Due to advancements on sensors ans batteries, those aerial robots became more accessible by the day. However, they are mostly destined to passive applications, such as surveillance and inspection, and to never physically interact with the environment. Aerial manipulation is a relatively new area that exploits the idea of using aerial robots fos tasks that demands physical interaction. This work presents three scenarios in aerial manipulation from the control perspective, and two of them are studied in depht. For the first scenario, it is investigated the possibilities and challenges of aerial manipulation pick-and-placing tasks based on Force and Torque (F/T) sensory feedback. A framework os proposed based on the feedback compensation of internal and external efforts measured by a six-axis F/T sensor, placed between the UAV and a robotic arm attached below it. An attitude controller that compensates for the sensed torques and a novel position controller are presented. For the second scenario, a control framework is proposed in order for the aerial manipulator to compensate generalized 3D forces applied at its end-effector. In this case, the system considered is composed of a UAV and one Degree of Freedom actuated rod. The frameworks capabilities are evaluated on simulations done with the MuJoCo physics engine. The proposed system could be useful on situations and tasks that are too risky for humans, such as working in high altitudes, or in hazardous ambients, as in nuclear power plants.